News and the British world the emergence of an imperial press system, 1876-1922 - Potter, Simon James (Oxford historical monographs., 2003)
During the late 19th and early 20th centuries, Britain, Canada, Australia, New Zealand, and South Africa were increasingly drawn together by an imperial press system. This is a scholarly study of the development of that system.